Evolutionary epidemiology predicts the emergence of glyphosate resistance in a major agricultural weed. Issue 3 (11th April 2019) - Comont, David; Hicks, Helen; Crook, Laura; Hull, Richard; Cocciantelli, Elise; Hadfield, Jarrod; Childs, Dylan; Freckleton, Robert; Neve, Paul
Summary: The evolution of resistance to herbicides is a striking example of rapid, human‐directed adaptation with major consequences for food production. Most studies of herbicide resistance are performed reactively and focus on post hoc determination of resistance mechanisms following the evolution of field resistance. If the evolution of resistance can be anticipated, however, pro‐active management to slow or prevent resistance traits evolving can be advocated. We report a national‐scale study that combines population monitoring, glyphosate sensitivity assays, quantitative genetics and epidemiological analyses to pro‐actively identify the prerequisites for adaptive evolution (directional selection and heritable genetic variation) to the world's most widely used herbicide (glyphosate) in a major, economically damaging weed species, Alopecurus myosuroides . Results highlighted pronounced, heritable variability in glyphosate sensitivity amongst UK A. myosuroides populations. We demonstrated a direct epidemiological link between historical glyphosate selection and current population‐level sensitivity, and show that current field populations respond to further glyphosate selection. This study provides a novel, pro‐active assessment of adaptive potential for herbicide resistance, and provides compelling evidence of directional selection for glyphosate insensitivity in advance of reports of field resistance. The epidemiological approach developed can provide a basis for further pro‐active study of resistance evolution across pesticide resistance disciplines. Abstract : See also the Commentary on this article by Baucom & Busi, 223 : 1056–1058 .